Occupational health hazards of stone quarry workers of Nagaland, India - Nutsolu Lohe; Sudipta Ghosh (Human Biology and Public Health, 2022)
Occupational health is a neglected public health issue among healthcare workers in developing countries.This study was conducted in Wokha district of Nagaland, North-East India. A total number of 152 Lotha male stone quarry workers with age cohort 18-60 years and an ethnicity and age matching 152 adult males as the controls were selected for the present study. Blood pressures (both systolic and diastolic), oxygen saturation, pulse rate and forced vital capacity (FVC) were measured on each participant.
Keywords: Lotha; Quarry workers; Blood pressure; Oxygen saturation; Pulse rate; Nagaland; India